Is it all about the self? The effect of self-control depletion on ultimatum game proposers - Halali, Eliran; Bereby-Meyer, Yoella; Ockenfels, Axel (Frontiers in Human Neuroscience, 2013)
In the ultimatum-game, as in many real-life social exchange situations, the selfish motive to maximize own gains conflicts with fairness preferences. In the present study we manipulated the availability of cognitive-control resources for ultimatum-game proposers to test whether preference for fairness is a deliberative cognitive-controlled act or an automatic act. In two experiments we found that a shortage in cognitive control (ego depletion) led proposers in the ultimatum game to propose significantly more equal split offers than non-depleted proposers. These results can be interpreted as resulting from an automatic concern for fairness, or from a greater fear of rejection, which would be in line with a purely self-interested response. To separate these competing explanations, in Experiment 2 we conducted a dictator-game in which the responder cannot reject the offer. In contrast to the increased fairness behavior demonstrated by depleted ultimatum-game proposers, we found that depleted dictator-game allocators chose the equal split significantly less often than non-depleted allocators. These results indicate that fairness preferences are automatically driven among ultimatum game proposers. The automatic fair behavior, however, at least partially reflects concern about self-interest gain. We discuss different explanations for these results.